2013
DOI: 10.1371/journal.pone.0062607
|View full text |Cite|
|
Sign up to set email alerts
|

The Stimulatory Adenosine Receptor ADORA2B Regulates Serotonin (5-HT) Synthesis and Release in Oxygen-Depleted EC Cells in Inflammatory Bowel Disease

Abstract: ObjectiveWe recently demonstrated that hypoxia, a key feature of IBD, increases enterochromaffin (EC) cell 5-HT secretion, which is also physiologically regulated by the ADORA2B mechanoreceptor. Since hypoxia is associated with increased extracellular adenosine, we wanted to examine whether this nucleotide amplifies HIF-1α-mediated 5-HT secretion.DesignThe effects of hypoxia were studied on IBD mucosa, isolated IBD-EC cells, isolated normal EC cells and the EC cell tumor derived cell line KRJ-1. Hypoxia (0.5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…Our data showed that the immunoexpression of ADORA2B was correlated with HIF-1α expression in primary OSCCs (Additional file 1 ). HIF-1α is a common transcription factor induced by ADORA2B activation in inflammatory bowel disease and urologic diseases [ 37 , 38 ]. Based on these findings, we observed the expression status of HIF-1α in the ADORA2B knockdown cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that the immunoexpression of ADORA2B was correlated with HIF-1α expression in primary OSCCs (Additional file 1 ). HIF-1α is a common transcription factor induced by ADORA2B activation in inflammatory bowel disease and urologic diseases [ 37 , 38 ]. Based on these findings, we observed the expression status of HIF-1α in the ADORA2B knockdown cells.…”
Section: Discussionmentioning
confidence: 99%
“…The opposite is true for increased SERT in platelet membranes, resulting in higher reuptake and reduced serotonin levels in the bloodstream [ 29 ]. Altered motility causing hypoxia in patients with IBD was shown to induce serotonin synthesis by stimulating adenosine receptors, leading to diarrhea [ 30 ].…”
Section: The Role Of Serotoninmentioning
confidence: 99%
“…Activation of A 2B AR via MAPK/CREB and TPH-1 signaling amplifies the effect of hypoxia in human EC cells. 129 Overall, effects of adenosine in IBD are very complex, and much more work needs to be done, but targeting this pathway in EC cells is of potential interest as a therapeutic target in IBD.…”
Section: 0 Adenosinergic Drugsmentioning
confidence: 99%